2020
DOI: 10.1080/09168451.2020.1783197
|View full text |Cite
|
Sign up to set email alerts
|

MiR-216a-3p regulates the proliferation, apoptosis, migration, and invasion of lung cancer cells via targeting COPB2

Abstract: Effect of miR-216a-3p on lung cancer hasn’t been investigated. Here, we explored its effects on lung cancer. MiR-216a-3p expression in lung cancer tissues and cells was detected by RT-qPCR. The target gene of miR-216a-3p was predicted by bioinformatics and confirmed by luciferase-reporter assay. After transfection, cell viability, migration, invasion, proliferation, and apoptosis were detected by MTT, scratch, transwell, colony formation, and flow cytometry. The expressions of COPB2 and apoptosis-related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Further studies revealed that the BMSC-derived exosome miR-4461 downregulated COPB2 and inhibited cell migration and invasion. Similar to the observations on miR-4461 in CRC, miR-335-3p and miR-216a-3p have been found to target the 3′UTR of COPB2, which led to the inhibition of COPB2 in lung adenocarcinoma (LUAD) [18] and lung cancer [17] cell lines, respectively.…”
Section: Functions Associated With Copb2supporting
confidence: 77%
See 1 more Smart Citation
“…Further studies revealed that the BMSC-derived exosome miR-4461 downregulated COPB2 and inhibited cell migration and invasion. Similar to the observations on miR-4461 in CRC, miR-335-3p and miR-216a-3p have been found to target the 3′UTR of COPB2, which led to the inhibition of COPB2 in lung adenocarcinoma (LUAD) [18] and lung cancer [17] cell lines, respectively.…”
Section: Functions Associated With Copb2supporting
confidence: 77%
“…COPB2 overexpression has been reported in various kinds of cancers (Table 1). Generally, the involvement of COPB2 in tumor progression has been found to be related to the regulation of upstream genes, such as the Sensitive to apoptosis gene (SAG or RNF7) [12] and Yes-associated protein 1 (YAP1) [13]; the activation of receptor tyrosine kinase (RTK) [14] and c-jun N-terminal kinase (JNK)/c-Jun signaling pathways [15]; and the targeting of microRNAs [16][17][18] (Fig. 1).…”
Section: Functions Associated With Copb2mentioning
confidence: 99%
“…Our results suggest that let-7a targets COPB2, which leads to differential expression after chrysin treatment in GC cells. A previous study indicated that the expression of COPB2 is associated with cell growth, apoptosis, migration and invasion, functioning through a miR-216a manner, in lung cancer (8). Our results suggested that expression of COPB2 was regulated by H19/let-7 axis in GC cells (Figure 7).…”
Section: Discussionsupporting
confidence: 61%
“…Coatomer protein complex subunit beta 2 (COPB2) is a protein that functions to transport other proteins as vesicles from the endoplasmic reticulum to Golgi apparatus ( 5 ). Recently, numerous reports have indicated that COPB2 is abnormally expressed in colorectal cancer (CRC), cholangiocellular carcinoma and lung cancer ( 6 8 ). Previous studies have indicated that the reduction of COPB2 expression inhibited cell growth and induced apoptosis through the JNK/c-Jun signaling pathway in RKO and HCT116 cells ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely established that miRNAs serve critical roles in the regulation of several biological process, including proliferation, differentiation, apoptosis, tumorigenesis and metastasis (6,12,13). Furthermore, miRNAs may predict overall prognosis in certain types of cancer, including lung cancer (14), gastric cancer (15) and CRC (16). Previous studies suggested that miR-590 is abnormally expressed in CRC (5,17); however, the mechanism underlying the action of miR-590-5p in the pathogenesis of CRC, as well as its potential gene target have not been identified.…”
Section: Introductionmentioning
confidence: 99%